THE EVALUATION OF ORGANIZATIONAL CULTURE COMMUNICATION THROUGH BOARD GAME ACTIVITY - Sorakraikitikul, Monthon; Supanan, Siriluk (Business Administration and Management Journal Review, 2020)
The purpose of this research is to evaluation board game activity to communicate corporate culture. The research applied qualitative research to assess 8 factors of success. The data collected by review documentary and in-depth interview all stakeholders i.e. 3 facilitators, 6 participants, and 2 supervisors of participants. Overall results revealedthe factor of success composed of (1) content (2) material (3) learning methodology (4) environment (5) learning approach. On contradictory, the failure factors came from (1) learning objective (2) instructor/facilitator capability from in an adequate selection process(3) and how to implement in theworking environment, asparticipants were not informed clearly about purpose andthe long-term impact, thus the activity may not meet the same expectation.